The use of biomarkers in the diagnosis and management of emergency medical conditions - Aljefri, Ahmed Amin; Alharthi, Mazen Saud; Almadari, Farhan Mufarreh; Alazwari, Hassan Abdualmohsin; Alshahrani, Zafer Ali; Alanazi, Abdullah Abdulelah; Al Gadani, Afnan Qasem; Aljawad, Ahmed Ali; Qattan, Faris Mohammed; Shuraym, Abdulrahman Hassan; Almutary, Aisha Nour (International Journal Of Community Medicine And Public Health, 2023)
The use of biomarkers in emergency situations represents a change in modern healthcare. This review examines their impact in emergencies focusing on how they improve the accuracy of diagnoses, provide insights into prognosis and aid in treatment decisions. Notably troponins (I and T) are effective in diagnosing myocardial infarction enabling targeted interventions and risk assessment for cardiovascular emergencies. In cases of sepsis procalcitonin helps distinguish infections and influences decisions about therapy, which is crucial for global efforts against resistance. S100B, a biomarker used in emergencies assists in prioritizing cases of brain injury. To prevent harm, serum markers like creatinine and cystatin C guide interventions for hepatic emergencies. For trauma and hematological emergencies D dimer and lactate provide prognostic information. Ongoing research is exploring biomarkers well as the integration of artificial intelligence offering promising advancements for the future. The clinical significance of biomarkers highlights a commitment to approaches that contribute to the ever-evolving field of emergency medicine and ultimately enhance patient care.